Antagonist Test of Bacillus subtilis ATTC 6633 and Trichoderma harzianum on the Growth of Magnaphorte oryzae on Several Varieties of Priming Rice Seeds - Feskaharny Alamsjah; Zozy Aneloi Noli; Hesti Dwi Marcellinna; Anthoni Agustien; Suwirmen; Kurniadi Ilham (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Priming is a seed-soaking technique to increase seed viability and also suppress pathogens' growth. Magnaporthe oryzae is one of the pathogens in rice plants that causes leaf blast disease. The high rice consumption each year in Indonesia is not proportional to the amount of rice plant production, which is affected by the growth of pathogenic fungi. This study aims to determine the viability and percentage inhibition of Bacillus subtilis and Trichoderma harzianum against the growth of the pathogenic fungus Magnaporthe oryzae on local West Sumatra rice varieties Ceredek, Pandan Pulau, and Batang Sungkai. The research was conducted by testing the viability of microbes by counting the number of colonies and testing microbial antagonists with the Dual Culture method on seven days of observation. The results showed that Bacillus subtilis and Trichoderma harzianum could inhibit the growth of the pathogen M. oryzae, which causes leaf blast disease. The viability of Bacillus subtilis after biopriming for 48 hours was most significant on Ceredek variety, which was 15.9x106 cfu/g, and for Trichoderma harzianum on Pandan Pulau variety, which was 0.4x106 cfu/g. The most significant inhibition percentage of Bacillus subtilis and Trichoderma harzianum was obtained in Ceredek rice with a value of 30.13% (medium category) and 63.04% (high category).